State history. Grand Coulee dam. Ice breaking. 1937-02-27 (1937)
Ice is broken by clamshell. - Bucket on crane on barge clears channel as spring break-up nears. - The spring break-up of ice in the Columbia river was but a few hours away, it seemed today, as the MWAK started smashing the big ice cap just downstream from the slots in the dam.